Conservative Surgery for Early Cervical Cancer - Rema, P. (Indian J Surg Oncol, 2015)
There is a rising incidence of early cervical cancer in young patients as a result of screening and early detection. Treatment of cervical cancer by surgery or radiotherapy results in permanent infertility which affects the quality of life of cancer survivors. Now with improved survival rates among early cervical cancer patients, conservative surgery aiming at fertility preservation in those desiring future pregnancy is an accepted treatment. Conservative surgery is possible in early cervical cancer including micro invasive cancer and stage IB cancers less than 2 cm. Stage IA1 cervical cancer is treated effectively by cervical conisation. In stage IA2 cancers and stage IB1 cancers less than 2 cm the fertility preservation surgery is radical trachelectomy. Radical trachelectomy removes the cervix with medial parametrium and upper 2 cm vaginal cuff retaining the uterus and adnexa to allow future pregnancy. Radical trachelectomy is a safe procedure in selected patients with cancer cervix with acceptable oncologic risks and promising obstetric outcome. It should be avoided in tumours larger than 2 cm and aggressive histologic types. This article focuses on the current options of conservative surgery in early cervical cancer.